Redox cycling of iridium(III) complexes gives versatile materials for photonics applications. (26th February 2016) - Morris, Collin D.; Spulber, Mariana; Neuburger, Markus; Palivan, Cornelia G.; Constable, Edwin C.; Housecroft, Catherine E.
Graphical abstract: The synthesis and crystal structure of the new anionic complex [Ir(ppy)2 (cat)] − are reported; this complex is unstable towards oxidation and the photophysical, electrochemical, and spectroelectrochemical properties of the resultant neutral semiquinonate complex are presented. Abstract: The cyclometallated iridium(III) complex [Me4 N][Ir(ppy)2 (cat)] (Hppy = 2-phenylpyridine; H2 cat = benzene-1, 2-diol) has been prepared under inert atmosphere and has been structurally characterized by single crystal X-ray diffraction. Under ambient conditions, the fully reduced complex (as formulated) undergoes rapid one-electron oxidation both in solution and in the solid state to a species containing a semiquinone ligand. The resultant neutral complex [Ir(ppy)2 (sq)] (sq =  o -semiquinone) was also prepared by exposing the reaction mixture to O2 during the course of the reaction. Electron paramagnetic resonance (EPR) spectroscopy confirms the diamagnetic nature of the complex [Me4 N][Ir(ppy)2 (cat)] and indicates that the unpaired electron in [Ir(ppy)2 (sq)] resides primarily on the sq ligand. The photophysical, electrochemical, and spectroelectrochemical properties of [Ir(ppy)2 (sq)] were investigated and reveal the changes in absorption as the complex is converted into the catecholate and quinone forms.